Persepsi Kegunaan dan kemudahan menggunakan terhadap Niat Menggunakan Mobile Payment dimasa Pandemi Covid-19 - Huddin, Muhammad Nurhaula; masitoh, Martina rahmawati (AL-QARDH, 2021)
Technological developments have changed the human behavior to consume products and services, from offline transactions to online transactions. The purpose is to examine the impact of perceived usefulness and perceived ease of use on attitude and examine its impact on intention to use mobile payments. The population in this study are customers who use mobile payment in Banten Province, especially Gopay and OVO. This study uses purposive sampling technique in determining the research sample. In this study, we obtained 243 respondents from mobile payment users in Banten Province. Using partial least square structural equation modeling (PLS-SEM), the researcher found that there is a significant influence between perceived usefulness and ease of use on attitudes towards mobile payments. This study also found that attitudes have a significant influence on intention to use mobile payments.